Railway heritage and industrial archaeology in the state of São Paulo (Brazil): The Railway Memory Project - Sanchiz, Juan Manuel Cano [UNESP] (My University, 2015)
The Projeto Memória Ferroviária (Railway Memory Project, UNESPFAPESP) is a cross-disciplinary research project that turns the railway heritage of the São Paulo state (Brazil) into a laboratory for testing new methodologies, tools and strategies regarding the research, management, dissemination and activation of the contemporary cultural heritage. This paper offers, in the first place, a brief view of the mentioned project. Secondly, the text presents the preliminary results achieved with the recent opening of a research line in Industrial Archaeology in the general framework of the Railway Memory Project, focused on the survey, analysis and interpretation of a certain area of the workshops built by the Companhia Paulista de Estradas de Ferro (Paulista Railway Co.) in Jundiaí city. Finally, this article intends to defend the contribution of Archaeology to the understanding of the recent past, as well as to promote new crossdisciplinary working ways that, based on methodological interaction, are capable to produce knowledge advancement and new resources from cultural heritage.
Patrimonio ferroviario y arqueología industrial en el estado de São Paulo (Brasil): El Projeto Memória Ferroviária
Keywords: Cross-disciplinarity; Industrial archaeology; Jundiaí's FEPASA complex; Railway heritage; Railway memory project